Cover Image Volume 49, Issue 2. (15th January 2019) - Martens, Andreas; Book, Matthias; Gruhn, Volker
Abstract : The cover image is based on the Special Issue Paper A data decomposition method for stepwise migration of complex legacy data by Andreas Martens et al., https://doi.org/10.1002/spe.2647 .